Acupuncture as an adjunctive therapy for gastric ulcer: A modified Delphi consensus study - Lu-qiang Sun; Fang-li Luo; Shuai Chen; Qian-hua Zheng; Lu Wang; Yu-jun Hou; Kai Wang; Jun-peng Yao; Xiang-yun Yan; Yun-zhou Shi; Ying Li (Elsevier, 2023)
Background: Acupuncture is often used as an adjunctive therapy for gastric ulcer (GU). However, there is still a lack of evidence on the appropriate and optimal interventions for acupuncture. This study aimed to optimize the acupuncture treatment of gastric ulcers based on expert consensus for guiding acupuncturists in clinical practice. Methods: To conduct this study, research evidence was gathered from databases in both Chinese and English. After discussion, preliminary clinical questions were developed. Following three rounds of multidisciplinary clinical expert consultation, the initial consensus questionnaire was formed after testing and modification by team members. A Delphi consensus was ultimately reached to answer the questionnaire and develop guidance for acupuncture treatment. A 9-point Likert-type scale was used to measure the agreement of expert consensus, where a score of 80% between 7 and 9 was defined as "agreement." Results: After two rounds of Delphi voting, a total of 35 items reached an agreement. These items can be roughly divided into 6 domains. According to expert consensus, the application of acupuncture for gastric ulcer should follow a semistandardized approach. Based on the syndrome differentiation, the main acupoints recommended are Zusanli (ST36), Zhongwan (CV12), Neiguan (PC6), and Sanyinjiao (SP6), while the adjunct acupoints include Taichong (LR3), Guanyuan (CV4), Xuehai (SP10), and Taixi (KI3). In the experience of experts, adverse events associated with acupuncture are typically mild and often manifest as subcutaneous hematomas. Conclusion: There is a lack of definitive acupuncture guidelines that can effectively determine the optimal therapeutic approach for the treatment of gastric ulcer. This expert consensus provides recommendations for clinical research and practice of acupuncture, with a particular focus on the selection of acupoints. However, further exploration through rigorous studies is necessary due to the limited availability of clinical evidence.